Classic bladder exstrophy: Frequent 22q11.21 duplications and definition of a 414 kb phenocritical region. Issue 6 (25th April 2014) - Draaken, Markus; Baudisch, Friederike; Timmermann, Bernd; Kuhl, Heiner; Kerick, Martin; Proske, Judith; Wittler, Lars; Pennimpede, Tracie; Ebert, Anne‐Karoline; Rösch, Wolfgang; Stein, Raimund; Bartels, Enrika; et al.
<x xml:space="preserve">Abstract</x> Background Classic bladder exstrophy (CBE) is the most common form of the bladder exstrophy and epispadias complex. Previously, we and others have identified four patients with a duplication of 22q11.21 among a total of 96 unrelated CBE patients. Methods Here, we investigated whether this chromosomal aberration was commonly associated with CBE/bladder exstrophy and epispadias complex in an extended case‐control sample. Multiplex ligation‐dependent probe amplification and microarray‐based analysis were used to identify 22q11.21 duplications in 244 unrelated bladder exstrophy and epispadias complex patients (including 217 CBE patients) and 665 healthy controls. Results New duplications of variable size were identified in four CBE patients and one control. Pooling of our previous and present data (eight duplications in 313 CBE patients) yielded a combined odds ratio of 31.86 (95% confidence interval, 4.24–1407.97). Array‐based sequence capture and high‐throughput targeted re‐sequencing established that all breakpoints resided within the low‐copy repeats 22A to 22D. Comparison of the eight duplications revealed a 414 kb phenocritical region harboring 12 validated RefSeq genes. Characterization of these 12 candidate genes through whole‐mount in situ hybridization of mouse embryos at embryonic day 9.5 suggested that CRKL, THAP7, and LZTR1 are CBE candidate genes. Conclusion Our data suggest that duplication of 22q11.21 increases CBE risk and implicate a phenocritical region in disease formation. Birth Defects Research (Part A) 100:512–517, 2014. © 2014 Wiley Periodicals, Inc.